2012
DOI: 10.1186/1750-2187-7-7
|View full text |Cite
|
Sign up to set email alerts
|

Akt (protein kinase B) isoform phosphorylation and signaling downstream of mTOR (mammalian target of rapamycin) in denervated atrophic and hypertrophic mouse skeletal muscle

Abstract: BackgroundThe present study examines the hypothesis that Akt (protein kinase B)/mTOR (mammalian target of rapamycin) signaling is increased in hypertrophic and decreased in atrophic denervated muscle. Protein expression and phosphorylation of Akt1, Akt2, glycogen synthase kinase-3beta (GSK-3beta), eukaryotic initiation factor 4E binding protein 1 (4EBP1), 70 kD ribosomal protein S6 kinase (p70S6K1) and ribosomal protein S6 (rpS6) were examined in six-days denervated mouse anterior tibial (atrophic) and hemidia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 88 publications
(108 reference statements)
2
7
0
Order By: Relevance
“…7F, I). Similar results were also reported by Norrby et al (2012) and MacDonald et al (2014). Due to the high levels of total proteins, it is likely that the phosphorylation rates of Akt in denervated muscles were calculated low even immediately after heat stress.…”
Section: Effect Of Heat Stress On Protein Synthesis In Denervated Solsupporting
confidence: 88%
“…7F, I). Similar results were also reported by Norrby et al (2012) and MacDonald et al (2014). Due to the high levels of total proteins, it is likely that the phosphorylation rates of Akt in denervated muscles were calculated low even immediately after heat stress.…”
Section: Effect Of Heat Stress On Protein Synthesis In Denervated Solsupporting
confidence: 88%
“…UDD is known to induce a transient hypertrophy,18, 19 yet, the trigger for this hypertrophy response was unknown. We show that this trigger is the passive, cyclic stretch of the denervated hemidiaphragm, imposed by the contracting contralateral diaphragm.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, we turned to unilateral diaphragm denervation (UDD) which induces a transient but strong hypertrophy response in the denervated, inactive hemidiaphragm. 18,19 This makes UDD ideal for directly testing the role of titin-based mechanosensing in muscle hypertrophy. UDD was applied in two mouse models in which titin stiffness is genetically altered: the RBM20 ΔRRM model.…”
Section: Introductionmentioning
confidence: 99%
“…Inactivation of AKT has been suggested as a permissive step for MuRF1 and Fbxo32 expression(Glass 2003), although in vivo MuRF1 induction may occur in conjunction with high levels of AKT phosphorylation(Machida et al 2012;Norrby et al 2012). Food deprivation induces MuRF1 and Fbxo32 expression concomitant with reduced AKT phosphorylation, and the sensitivity of skeletal muscle to length of food deprivation decreases with age: we have previously shown that 8 h of fasting during light hours is sufficient to induce MuRF1 and Fbxo32 expression mRNA in skeletal muscles of juvenile (3 weeks) mice, but not young adult (3 m) mice(Shavlakadze et al 2013b).…”
mentioning
confidence: 99%